Animal Models to Study the Role of Long-Term Hypergastrinemia in Gastric Carcinogenesis. (24th November 2010) - Fossmark, Reidar; Qvigstad, Gunnar; Martinsen, Tom Chr.; Hauso, Øyvind; Waldum, Helge L.
Abstract : Patients with chronic hypergastrinemia due to chronic atrophic gastritis or gastrinomas have an increased risk of developing gastric malignancy, and it has been questioned whether also patients with hypergastrinemia caused by long-term use of acid inhibiting drugs are at risk. Gastric carcinogenesis in humans is affected by numerous factors and progresses slowly over years. When using animal models with the possibility of intervention, a complex process can be dissected by studying the role of hypergastrinemia in carcinogenesis within a relatively short period of time. We have reviewed findings from relevant models where gastric changes in animal models of long-term hypergastrinemia have been investigated. In all species where long-term hypergastrinemia has been induced, there is an increased risk of gastric malignancy. There is evidence that hypergastrinemia is a common causative factor in carcinogenesis in the oxyntic mucosa, while other cofactors may vary in the different models.